New approach methodologies to enhance human health risk assessment of immunotoxic properties of chemicals — a PARC (Partnership for the Assessment of Risk from Chemicals) project - Snapkow, Igor; Smith, Nicola M.; Arnesdotter, Emma; Beekmann, Karsten; Blanc, Etienne B.; Braeuning, Albert; Corsini, Emanuela; Sollner Dolenc, Marija; Duivenvoorde, Loes P. M.; Sundstøl Eriksen, Gunnar; Franko, Nina; Galbiati, Valentina; et al. (Frontiers in Toxicology, 2024)
As a complex system governing and interconnecting numerous functions within the human body, the immune system is unsurprisingly susceptible to the impact of toxic chemicals. Toxicants can influence the immune system through a multitude of mechanisms, resulting in immunosuppression, hypersensitivity, increased risk of autoimmune diseases and cancer development. At present, the regulatory assessment of the immunotoxicity of chemicals relies heavily on rodent models and a limited number of Organisation for Economic Co-operation and Development (OECD) test guidelines, which only capture a fraction of potential toxic properties. Due to this limitation, various authorities, including the World Health Organization and the European Food Safety Authority have highlighted the need for the development of novel approaches without the use of animals for immunotoxicity testing of chemicals. In this paper, we present a concise overview of ongoing efforts dedicated to developing and standardizing methodologies for a comprehensive characterization of the immunotoxic effects of chemicals, which are performed under the EU-funded Partnership for the Assessment of Risk from Chemicals (PARC).